GAGASAN PENGATURAN HUKUM PEMERIKSAAN PERSEROAN TERBATAS (Suatu Evaluasi Normatif terhadap Pasal 138 - Pasal 141 Undang-Undang Nomor 40 Tahun 2007 tentang Perseroan Terbatas) - Muhammad Syaifuddin (Faculty of Law, Universitas Jenderal Soedirman, 2011)
Law No. 40 Year 2007 oblige good corporate governance. Practically, there is a chance to do wrongful act which cause bad corporate governance. Law No. 40 Year 2007 have some legal inconsistencies, so that cause uncertainty and unused legal practically. The idea of regulating on investigating of a company in forward has to develop of strengthening of legal certainty principle and legal utility principle (besides legal justice principle) which concrete in positive legal norms about performing, governing, investigating and post-investigating of a limited company by shares as a system. Then, the revising of positive legal norms about investigating of a limited company by shares consistently, which refers to the logics of legal rules. Keywords: the investigating, limited company by shares, normative evaluation, legal inconsistency